2022
DOI: 10.1002/oby.23577
|View full text |Cite
|
Sign up to set email alerts
|

The effects of time‐restricted eating and weight loss on bone metabolism and health: a 6‐month randomized controlled trial

Abstract: Objective: This study explored the impact of time-restricted eating (TRE) versus standard dietary advice (SDA) on bone health.Methods: Adults with ≥1 component of metabolic syndrome were randomized to TRE (ad libitum eating within 12 hours) or SDA (food pyramid brochure). Bone turnover markers and bone mineral content/density by dual energy x-ray absorptiometry were assessed at baseline and 6-month follow-up. Statistical analyses were performed in the total population and by weight loss response.Results: In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…In line with these findings, a longer-term (6 months) TRE intervention (employing a 12-h ad libitum eating window) had no unfavourable effects on bone metabolism (BTMs and bone-related hormones) or bone loss (total body BMC/BMD by DXA) compared with the provision of standard dietary advice for healthy eating, in individuals with at least one component of the metabolic syndrome (64) . Additional sub-analysis in participants who lost weight with either TRE or standard dietary advice (based on median body weight changes: ≥ 0•6 kg weight loss) found that those who lost weight by following SDA experienced a modest loss of total body BMC, which was supported by small, albeit non-significant increases in bone resorption (CTX).…”
Section: Interventional Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…In line with these findings, a longer-term (6 months) TRE intervention (employing a 12-h ad libitum eating window) had no unfavourable effects on bone metabolism (BTMs and bone-related hormones) or bone loss (total body BMC/BMD by DXA) compared with the provision of standard dietary advice for healthy eating, in individuals with at least one component of the metabolic syndrome (64) . Additional sub-analysis in participants who lost weight with either TRE or standard dietary advice (based on median body weight changes: ≥ 0•6 kg weight loss) found that those who lost weight by following SDA experienced a modest loss of total body BMC, which was supported by small, albeit non-significant increases in bone resorption (CTX).…”
Section: Interventional Studiessupporting
confidence: 68%
“…This study found that TRE had no impact on participants' body mass, lean mass, total body or . The primary outcomes of the included studies were changes in body weight (n 3; Barnosky et al (60) ; Lowe et al (61) ; Kotarsky et al (67) ), changes in body composition (n 1; Templeman et al (30) ), changes in insulin sensitivity (n 1; Stekovic et al (57) ), changes in components of energy balance and post-prandial metabolism (n 1; Templeman et al (30) ), change in the metabolic syndrome components (n 1; Papageorgiou et al (64) ) and changes in endothelium-dependent dilation (n 1; Martens et al (63) ).…”
Section: Interventional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analyses were carried out to assess the robustness of the summary estimates via the leave-one-out method [ 34 ]. Furthermore, additional analyses were conducted while upholding the prevailing health status of the participants included in the RCTs (i.e., overweight and/or obesity) [ 42 , 43 , 44 , 45 ] and the predominant TRE protocol (i.e., fasting window 16:8) [ 42 , 43 , 44 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…When RCTs reported results for different parameters of bone health [ 42 , 44 , 45 , 47 ], data were included according to the appropriate analysis. Where between-group MDs were displayed only graphically [ 43 ], data were extracted using online software (WebPlotDigitizer, assessed on 2 December 2023) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%